Prevalence of Latent Autoimmune Diabetes of Adult (LADA) among Type2 Diabetes Mellitus (D.M.2) in Karbala - Sawsan M. AL-Hasnawi; Salman A. AL-Jiboury (Kufa Journal for Nursing Sciences)
Objective: the aim of the study is to determine the prevalence of LADA among group of clinically diagnosed type 2 diabetes mellitus.